Applied behavior analysis as intervention for autism: definition, features and philosophical concepts - Síglia Pimentel Höher Camargo; Mandy Rispoli (Universidade Federal de Santa Maria (UFSM), 2013)
Autism spectrum disorder (ASD) is a lifelong pervasive developmental disorder with no known causes and cure. However, educational and behavioral interventions with a foundation in applied behavior analysis (ABA) have been shown to improve a variety of skill areas such as communication, social, academic, and adaptive behaviors of individuals with ASD. The goal of this work is to present the definition, features and philosophical concepts that underlie ABA and make this science an effective intervention method for people with autism.